Chronic Inflammatory Periodontal Disease in Patients Diagnosed with Human Immunodeficiency Virus/AIDS in Cienfuegos - Nivia Gontán Quintana; Alain Soto Ugalde; Elena Idaisy Otero Salabarría (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Background: human immunodeficiency virus increases patients´ susceptibility to infections. Consequently, a high incidence of periodontal diseases is observed among them. It is often associated with other lesions of the oral mucous. Objective: to determine the evolution of chronic inflammatory periodontal disease in patients diagnosed with human immunodeficiency virus/AIDS. Methods: a case series study involving HIV-positive patients who attended the Stomatology consultation in Cienfuegos was conducted. The Russell Periodontal Index and the Simplified Oral Hygiene Index were used. Patients were classified taking into account clinical and immunological categories. Statistical processing was performed through SPSS program version 15.0 and Chi-square tests were applied. Results: a high prevalence of chronic inflammatory periodontal disease was observed in patients with human immunodeficiency virus. Correlation with the oral hygiene of the patients studied was found. CD4 count showed no statistical significance in periodontal disease severity. All patients classified as A2 suffer from some stage of periodontal disease, which was the most affected clinical category in spite of presenting mild immunodeficiency. Conclusions: there is a high prevalence of chronic inflammatory periodontal disease in patients diagnosed with Human Immunodeficiency Virus in Cienfuegos and it is correlated with patient's oral hygiene.